DESAIN TUNING PID MENGGUNAKAN DIFFERENTIAL EVOLUTION (DE) UNTUK SISTEM PENGATURAN SUHU PADA INKUBATOR - Utama, Yoga Alif Kurnia; Dhaniswara , erwin (Foristek, 2023)
The temperature in the room is very dependent on the temperature outside the room. If the temperature outside is unstable, the impact will be reflected on the temperature instability in the room. This creates challenges in controlling room temperature that require a level of consistency, such as in a baby incubator machine, oven, or egg hatcher. Thus, a temperature regulation strategy is needed to overcome disturbances arising from external temperature fluctuations. This research proposes a solution through the use of innovative control methods, namely by making conventional PID control and PID Disturbance Observer. The value of the PID constant will use the Differential Evaluation (DE) method. Both will be tested on an incubator system through simulations at MATLAB2014a with performance index criteria in the form of ITAE. Interference will be introduced into the system by magnifying the temperature difference between inside and outside the incubator so that heat transfer occurs which will affect the temperature inside the incubator. The results showed that the ITAE value of the Distubance Observer PID control was 0.035, while the ITAE of conventional PID control was 0.242. This shows that the PID Disturbance Observer control is an effective control in controlling the temperature inside the incubator and maintaining that temperature from outside interference.